Defining diagnostic cutoffs in neurological patients for serum very long chain fatty acids (VLCFA) in genetically confirmed X-Adrenoleukodystrophy - Rattay, Tim W; Rautenberg, Maren; Söhn, Anne S; Hengel, Holger; Traschütz, Andreas; Röben, Benjamin; Hayer, Stefanie N; Schüle, Rebecca; Wiethoff, Sarah; Zeltner, Lena; Haack, Tobias B; Cegan, Alexander; et al. (Scientific reports, 2020)
X-linked Adrenoleukodystrophy (X-ALD) is caused by mutations in the ABCD1 gene resulting in the accumulation of very long chain fatty acids (VLCFA). X-ALD is the most common peroxisomal disorder with adult patients (male and female) presenting with progressive spastic paraparesis with bladder disturbance, sensory ataxia with impaired vibration sense, and leg pain. 80% of male X-ALD patients have an adrenal failure, while adrenal dysfunction is rare in women with X-ALD. The objective of this study was to define optimal serum VLCFA cutoff values in patients with X-ALD-like phenotypes for the differentiation of genetically confirmed X-ALD and Non-X-ALD individuals. Three groups were included into this study: a) X-ALD cases with confirmed ABCD1 mutations (n = 34) and two Non-X-ALD cohorts: b) Patients with abnormal serum VCLFA levels despite negative testing for ABCD1 mutations (n = 15) resulting from a total of 1,953 VLCFA tests c) Phenotypically matching patients as Non-X-ALD controls (n = 104). Receiver operating curve analysis was used to optimize VLCFA cutoff values, which differentiate patients with genetically confirmed X-ALD and Non-X-ALD individuals. The serum concentration of C26:0 was superior to C24:0 for the detection of X-ALD. The best differentiation of Non-X-ALD and X-ALD individuals was obtained with a cutoff value of < 1.0 for the C24:0/C22:0 ratio resulting in a sensitivity of 97%, a specificity of 94.1% and a positive predictive value (PPV) of 83.8% for true X-ALD. Our findings further suggested a cutoff of < 0.02 for the ratio C26:0/C22:0 leading to a sensitivity of 90.9%, a specificity of 95.0%, and a PPV of 80.6%. Pearson correlation indicated a significant positive association between total blood cholesterol and VLCFA values. Usage of serum VLCFA are economical and established biomarkers suitable for the guidance of genetic testing matching the X-ALD phenotype. We suggest using our new optimized cutoff values, especially the two ratios (C24:0/C22:0 and C26:0/C22:0), in combination with standard lipid profiles.
Keywords: Male; mutace; adrenoleukodystrofie; Fatty Acids; Adult; ženské pohlaví; ATP-Binding Cassette Transporters; Aged; Middle Aged; senzitivita a specificita; ABC transportéry; Biomarkers; Mutation; astrocyty; biologické markery; lidé středního věku; Humans; senioři; Adrenoleukodystrophy; Female; mastné kyseliny; dospělí; mužské pohlaví; Sensitivity and Specificity; lidé; Astrocytes